Testing an "in-out" targeting procedure for making subtle genomic modifications in mouse embryonic stem cells. - Valancius, V (1991)
We have introduced a 4-bp insertion into the hypoxanthine phosphoribosyltransferase (HPRT) gene of a mouse embryonic stem (ES) cell line by using an "in-out" targeting procedure. During the in step, a homologous integration reaction, we targeted a correcting plasmid to a partially deleted hprt- locus by using an integrating vector that carried a 4-bp insertion in the region of DNA homologous to the target locus. HPRT+ recombinants were isolated by direct selection in hypoxanthine-aminopterin-thymidine (HAT) medium. The HATr cell lines were then grown in medium containing 6-thioguanine (6-TG) to select for hprt- revertants resulting from the excision of the integrated vector sequences. The revertants were examined by Southern blot hybridization to determine the accuracy of this out reaction and the frequency of retaining the 4-bp modification in the genome. Of the 6-TGr colonies examined, 88% had accurately excised the integrated vector sequences; 19 of 20 accurate revertants retained the 4-bp insertion in the resulting hprt- gene. We suggest a scheme for making the in-out targeting procedure generally useful to modify the mammalian genome.